Spatial ecology and conservation of tigers and their prey in the Central Terai Landscape, India - Chanchani, Pranav, author; Noon, Barry, advisor; Bailey, Larissa, committee member; Crooks, Kevin, committee member; Hobbs, N. Thompson, committee member (Colorado State University. Libraries, 2016)
Remnant populations of the world’s ~3800 wild tigers (Panthera tigris) are generally small (< 20 adult individuals), subject to high rates of poaching, and confined to fragmented habitats with high levels of human disturbance. The species persistence requires an in-depth understanding of the suite of exogenous and endogenous factors that drive spatial heterogeneity in its occurrence and abundance. We intensively sampled tiger habitats in the populous 4500 km2 Central Terai Landscape along the India-Nepal border and investigated the following questions: (a) what is the relative influence of protection designation (protected area or multiple use forests), prey availability, patch connectivity, human presence and habitat quality on landscape and local-scale tiger occurrence; (b) how do these and other factors drive spatial heterogeneity in tiger density at broad and fine spatial scales; and (c) what are the relationships between landscape fragmentation, adult sex ratios, and inter-specific interactions? We found that tiger occupancy and abundance were similar or higher in multiple use forests with high human use, than in several protected areas. Further, the distribution and abundance of prey and key habitats such as tall grasslands, –rather than protection designation, were the best predictors of spatial heterogeneity in tiger occupancy and density. The co-occurrence of tigers and humans in areas with high human use may be facilitated by refugia habitats such as tall grasslands and temporal partitioning of use. Habitat connectivity promoted high occupancy only when all habitats connected by corridors were effectively protected. Finally, we documented exacerbated potential for inter- and intra-sex competition and reduced population fitness in small, isolated tiger populations with male-biased adult sex ratios. Overall, our study reveals that the establishment of protected areas alone may be an inadequate strategy to secure the future of wild tigers. We identified key ecological and anthropogenic factors that cumulatively enable the species persistence in populous human dominated landscapes.